(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The present study focuses on the evaluation of the mechanical properties degradation of Cr-coated Zr-alloy fuel cladding. The main objective of the work is to find a suitable methodology to evaluate the mechanical properties degradation of coated cladding by performing several separate effects experiments. Apart from the many positive effects of protective coatings on the overall cladding properties, coatings’ general disadvantage is their reduced ability to tolerate plastic strain. Therefore, coating cracks might occur in the first stage of the hypothetical Loss of Coolant Accident (LOCA). The study is unique because of the consideration of coating cracks. Prior to the high-temperature (HT) oxidation, samples were subjected to either a scratch test or burst test, resulting in the creation of coating defects. The subsequent evaluation of the obtained data consisted of wavelength dispersion spectroscopy (WDS) and optical microscopy analysis and hydrogen content measurements.